Wettability alteration implications on pore-scale multiphase flow in porous media using the lattice Boltzmann method. (December 2020) - Nemer, Mohamed N.; Rao, Parthib R.; Schaefer, Laura
Highlights: The relative importance and effects of the wettability-altered fraction, degree of wettability alteration, and accurate contact angle assignment are analyzed in terms of macroscale measurements and pore-scale fluid distributions. The fraction altered is the most important factor and results in a larger resistance to flow with implications on fluid entrapment patterns and connectivity. The effects of the degree of wettability alteration and contact angle assignment become more significant as the wettability-altered fraction increases. The degree of wettability alteration impacts the two phases to varying extents and is controlled by the fraction altered and the pore geometry. The strong interdependence between wettability heterogeneity and pore geometry is presented. Abstract: Multiphase flow in porous media is found in a variety of engineering problems, including in technologies focused on satisfying the energy needs of an expanding global population while minimizing the effects of human activity on climate change. The objective of this study is to provide a better understanding of the importance and interdependence of the wettability-altered fraction, the degree of wettability alteration, and the spatially-varying contact angle assignment in influencing the pore-scale and macroscale flow properties. In order to conduct this investigation and analyze the effects on the relative permeability curves and fluid configurations, the Shan-Chen multi-relaxation-time multicomponent lattice Boltzmann model with explicit forcing is utilized, and domains of increasing fractions of wettability-altered pores are generated. We find that the fraction altered, the degree of alteration, and the accurate contact angle assignment are all correlated, and play a role to varying extents in influencing the flow behavior and the resulting relative permeability curves. The fraction altered displays the strongest effect, and the effects of the degree of alteration and contact angle assignment become more significant when a larger fraction of the sample has undergone wettability alteration. A sample that has undergone fractional wettability alteration results in a larger resistance to the overall flow and more tortuous flow paths, at intermediate saturations, in comparison to a strongly water/oil wetting domain. In a high porosity domain that is becoming increasingly oil-wet, the degree of wettability alteration has a more pronounced effect on the flow behavior of the oil phase, whereas the flow of the water phase remains dictated by the large pore spaces and the regions of the domain that have not undergone wettability alteration until a significant fraction of the domain has been altered. Moreover, a spatially-varying contact angle assignment becomes more important for a system with a large distribution of contact angles. The results demonstrate the correlations between wettability alteration and pore geometry and highlight the need for an algorithm that captures the true time-dependent wettability state of a porous medium sample.